2020
DOI: 10.1590/0034-7167-2020-0110
|View full text |Cite
|
Sign up to set email alerts
|

Active ageing among elderly community members: structural equation modeling analysis

Abstract: Objective: to propose a structural model of active ageing among elderly community members based on the World Health Organization’s theoretical framework and to identify the most relevant determinants of active ageing to the proposed model. Methods: a cross-sectional and analytical study conducted with 957 elderly community members. Confirmatory factor analysis and structural equation modeling were performed. Results: the final measurement model was composed of the six determinants of active ageing: behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Further, ADL was significantly associated with active aging, which supports the findings of previous studies ( 24 , 44 , 45 ). ADL decline has been linked to lower physical activity, lower life satisfaction, and lower social participation, which are essential components of a low-level active aging state.…”
Section: Discussionsupporting
confidence: 91%
“…Further, ADL was significantly associated with active aging, which supports the findings of previous studies ( 24 , 44 , 45 ). ADL decline has been linked to lower physical activity, lower life satisfaction, and lower social participation, which are essential components of a low-level active aging state.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a structural model of active aging developed in a previous study, based on the theoretical framework of the WHO, 1 was used. 15 The instruments applied at a single moment to measure the determinants of the active aging model were defined considering the most used ones in gerontology and validated in Brazil ( Chart 1 ). 15 - 29 …”
Section: Methodsmentioning
confidence: 99%
“… 15 The instruments applied at a single moment to measure the determinants of the active aging model were defined considering the most used ones in gerontology and validated in Brazil ( Chart 1 ). 15 - 29 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, nationally representative analyses, based on the National Health Survey (PNS) conducted in 2013, found that active aging, defined in social, physical, intellectual, and work activity dimensions, demonstrated disparities between socioeconomic status, race, sex, and age 9 , 10 . Moreover, a local study conducted in Uberaba city (Minas Gerais State, Brazil) with 957 community-dwelling older adults proposed a structural active aging model and found that the most relevant determinant category was the health/social services determinants, followed by the social determinants 11 .…”
Section: Introductionmentioning
confidence: 99%